(untitled) (Revista Internacional de Folkcomunicação, 2020)
This article aims to analyze how Folkcommunication serves as a resistance strategy for marginalized groups, based on a case study of the community of Povoado Coqueiro, located in the Metropolitan Region of Aracaju (RMA). Semi-structured interviews collected in the community were analyzed in order to understand how waste pickers see the media process in the preservation of their identity. We found that mass communication follows a logic that does not match the cultural reality of the community and the local population remains indifferent in the construction of their own expressions of resistance. Aracaju; Crab; Folkcommunication; Identity; Marginalized groups.